Prevalence and Characteristics of Metabolic Syndrome Differ in Men and Women with Early Rheumatoid Arthritis. Issue 9 (28th August 2019) - Kuriya, B.; Schieir, O.; Valois, M. F.; Pope, J. E.; Boire, G.; Bessette, L.; Hazlewood, G.; Thorne, J. C.; Tin, D.; Hitchon, C.; Bartlett, S.; Keystone, E. C.; et al.
Abstract : Objective: Metabolic syndrome (MetS) prevalence in early rheumatoid arthritis (ERA) is conflicting. The impact of sex, including menopause, has not been described. We estimated the prevalence and factors associated with MetS in men and women with ERA. Methods: A cross‐sectional study of the Canadian Early Arthritis Cohort (CATCH) was performed. Participants with baseline data to estimate key MetS components were included. Sex‐stratified logistic regression identified baseline variables associated with MetS. Results: The sample included 1543 participants; 71% were female and the mean age was 54 (SD 15) years. MetS prevalence was higher in men 188 (42%) than women 288 (26%, P < 0.0001) and increased with age. Frequent MetS components in men were hypertension (62%), impaired glucose tolerance (IGT, 40%), obesity (36%), and low high‐density lipoprotein cholesterol (36%). Postmenopausal women had greater frequency of hypertension (65%), IGT (32%), and high triglycerides (21%) compared with premenopausal women ( P < 0.001). In multivariate analysis, MetS was negatively associated with seropositivity and pulmonary disease in men. Increasing age was associated with MetS in women. In postmenopausal women, corticosteroid use was associated with MetS. Psychiatric comorbidity was associated with MetS in premenopausal women. MetS status was not explained by disease activity or core RA measures. Conclusion: The characteristics and associations of MetS differed in men and women with ERA. Sex differences, including postmenopausal status, should be considered in comorbidity screening. With this knowledge, the interplay of MetS, sex, and RA therapeutic response on cardiovascular outcomes should be investigated.